2014
DOI: 10.1186/s12968-014-0072-2
|View full text |Cite
|
Sign up to set email alerts
|

Value of additional strain analysis with feature tracking in dobutamine stress cardiovascular magnetic resonance for detecting coronary artery disease

Abstract: BackgroundDobutamine stress cardiovascular magnetic resonance (DS-CMR) has been established for the detection of coronary artery disease (CAD). The novel technique feature tracking (FT) analyses left ventricular circumferential strain (Ecc) thus offering detailed information about myocardial deformation. The purpose of this study was to evaluate FT based Ecc for the detection of myocardial ischemia during DS-CMR.MethodsA total of 25 patients (18 males; mean age 64 ± 10 years) with suspected or known CAD underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 17 publications
1
42
0
1
Order By: Relevance
“…Reproducibility and sample sizes may therefore be different in patients or when image quality is reduced. However, although dobutamine stimulation may reduce image quality, a previous MR-FT study in a patient group with coronary artery disease even demonstrated improved MR-FT reproducibility during dobutamine exposure as compared to measurements at rest (23). …”
Section: Discussionmentioning
confidence: 97%
“…Reproducibility and sample sizes may therefore be different in patients or when image quality is reduced. However, although dobutamine stimulation may reduce image quality, a previous MR-FT study in a patient group with coronary artery disease even demonstrated improved MR-FT reproducibility during dobutamine exposure as compared to measurements at rest (23). …”
Section: Discussionmentioning
confidence: 97%
“…This is in line with previous evidence from myocardial tagging suggesting that quantification of wall motion with strain enhances diagnostic accuracy when compared with visual analysis for the detection of ischemia during high-dose dobutamine stress. 32 On the basis of CMR-FT, Schneeweis et al 23 have reproduced an important finding that quantitative impairments of myocardial strain defined by strain encoding imaging already occur at intermediate dobutamine levels. 33 Because CMR-FT does not require the acquisition of extra sequences (when compared with strain encoding imaging) and the risk of adverse events when diagnosing coronary disease at intermediate dobutamine levels is low, there could be clinical benefit of using CMR-FT during ischemia testing.…”
Section: Ventricular Performancementioning
confidence: 99%
“…30,31 Assessment of ventricular deformation at rest and with inotropic stimulation using dobutamine has provided clinically relevant data in health 18,20 and disease states. 23, 24 Schneeweis et al 23 demonstrated the ability to use circumferential short-axis strain to identify inducible ischemia during intermediate and high-dose dobutamine stimulation. This is in line with previous evidence from myocardial tagging suggesting that quantification of wall motion with strain enhances diagnostic accuracy when compared with visual analysis for the detection of ischemia during high-dose dobutamine stress.…”
Section: Ventricular Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances reported in the journal have included improved flow mapping, [13] real-time imaging, [4] T1 mapping, [57] simulations, [8, 9] perfusion, [1012] coronary imaging, [13] diffusion tensor imaging, [1416] feature tracking, [1720] and strain assessment. [21, 22] The full breadth of new developments is described in the papers in the section.…”
Section: Technical Developmentsmentioning
confidence: 99%